2014
DOI: 10.1111/jipb.12210
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification, evolution, and expression analysis of RNA‐binding glycine‐rich protein family in maize

Abstract: The RNA-binding glycine-rich protein (RB-GRP) family is characterized by the presence of a glycine-rich domain arranged in (Gly)n-X repeats and an RNA-recognition motif (RRM). RB-GRPs participate in varied physiological and biochemical processes especially in the stress response of plants. In this study, a total of 23 RB-GRPs distributed on 10 chromosomes were identified in maize (Zea mays L.), and they were divided into four subgroups according to their conserved domain architecture. Five pairs of paralogs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 47 publications
3
43
0
Order By: Relevance
“…The remaining 14 proteins (IVa = 6; IVb = 2; IVc = 2; IVd = 4) were selected to represent the OsRBG class (Table S3). Twenty-three RBGs (IVa = 6; IVb = 6; IVc = 2; IVd = 9) were previously identified in the maize genome by whole-genome sequence analysis (Zhang et al 2014). Relying on the results of Zhang et al (2014), we did not screen the maize whole genome; instead, we performed an ortholog search of RGAP and POG databases using the 23 ZmRBGs.…”
Section: Genome-wide Identification Selection Classification and Namentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining 14 proteins (IVa = 6; IVb = 2; IVc = 2; IVd = 4) were selected to represent the OsRBG class (Table S3). Twenty-three RBGs (IVa = 6; IVb = 6; IVc = 2; IVd = 9) were previously identified in the maize genome by whole-genome sequence analysis (Zhang et al 2014). Relying on the results of Zhang et al (2014), we did not screen the maize whole genome; instead, we performed an ortholog search of RGAP and POG databases using the 23 ZmRBGs.…”
Section: Genome-wide Identification Selection Classification and Namentioning
confidence: 99%
“…Twenty-three RBGs (IVa = 6; IVb = 6; IVc = 2; IVd = 9) were previously identified in the maize genome by whole-genome sequence analysis (Zhang et al 2014). Relying on the results of Zhang et al (2014), we did not screen the maize whole genome; instead, we performed an ortholog search of RGAP and POG databases using the 23 ZmRBGs. This search indicated that the orthologs of U11/U12-31 K (GRMZM2G053223), TBP-associated factor 15B (TAF15B; GRMZM2G097775), UBP1-associated protein 2 (UBA2; GRMZM2G132465) and nucleolin-like (GRMZM2G001850 and GRMZM2G131943) proteins were included in the ZmRBG class.…”
Section: Genome-wide Identification Selection Classification and Namentioning
confidence: 99%
See 3 more Smart Citations